2022
DOI: 10.3389/fimmu.2022.904418
|View full text |Cite
|
Sign up to set email alerts
|

3D Collagen Fiber Concentration Regulates Treg Cell Infiltration in Triple Negative Breast Cancer

Abstract: BackgroundTriple negative breast cancer (TNBC) is characterized by poor prognosis and a lack of effective therapeutic agents owing to the absence of biomarkers. A high abundance of tumor-infiltrating regulatory T cells (Tregs) was associated with worse prognosis in malignant disease. Exploring the association between Treg cell infiltration and TNBC will provide new insights for understanding TNBC immunosuppression and may pave the way for developing novel immune-based treatments.Materials and MethodsPatients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…This decrease in the proliferation of activated T-cells correlated well with the previously discussed activation states of T-cells ( Figure 4A-C ). Our finding is in agreement with another study that demonstrated that increased collagen density can diminish T-cell proliferation [11, 62]. Conversely, a study using 3D alginate hydrogels revealed enhanced T-cell proliferation in stiffer hydrogels [22].…”
Section: Resultssupporting
confidence: 93%
“…This decrease in the proliferation of activated T-cells correlated well with the previously discussed activation states of T-cells ( Figure 4A-C ). Our finding is in agreement with another study that demonstrated that increased collagen density can diminish T-cell proliferation [11, 62]. Conversely, a study using 3D alginate hydrogels revealed enhanced T-cell proliferation in stiffer hydrogels [22].…”
Section: Resultssupporting
confidence: 93%
“…Moreover, the ECM stiffness was shown to modulate the phenotype of CD4+ and CD8+ cells in the same study. In parallel, 3D collagen gels evidenced that increased collagen concentrations promoted the infiltration of regulatory T cells, in agreement with the altered ECM signaling correlated with T reg content in breast cancers [ 106 ].…”
Section: Future Is Coming Giving a New Dimension To The Tradementioning
confidence: 77%
“…Blocking immune cell expression in the tumor microenvironment and preventing their full role can lead to tumor development and metastasis. While internal genetic changes primarily lead to tumor cell formation, the tumor microenvironment, in ammatory processes, and immune response play crucial roles in tumor progression [11]. Sokratos [12] found that the tumor stroma plays a critical role in tumor occurrence, development, invasion, metastasis, and treatment sensitivity.…”
Section: Discussionmentioning
confidence: 99%